Latent Tuberculosis Infection in a Migrant Agricultural Community in Baja California, Mexico - Garfein, Richard S. (Springer US, 2010)
The objectives were to estimate the prevalence and identify correlates of latent tuberculosis infection (LTBI) among residents of a migrant agricultural community in San Quintín, Baja-California, Mexico. Residents completed a questionnaire and had their blood tested for LTBI using the QuantiFERON(®)-TB Gold In-Tube (QFT) assay. Among 133 participants, 39.8% (95% CI 31.5–48.7%) tested QFT-positive. Having crossed the U.S.-Mexican border since living in San Quintin (P = 0.03), consuming unpasteurized milk (P = 0.02) and receiving health care at IMSS-Oportunidades in the last 6 months (P = 0.03) were independently associated with QFT-positivity. High LTBI prevalence in this community emphasizes the need for TB education and LTBI treatment for its residents. Association with travel to the U.S. suggests the potential for TB transmission across borders. Higher QFT-positivity among those consuming unpasteurized milk could indicate M. bovis infection, previously reported among Mexican migrants living in U.S. border cities.